P.067 A worldwide survey of physician approaches to patients with acutely symptomatic carotid stenosis ("hot carotid"). (November 2021) - Ganesh, A; Jewett, G; Campbell, DJ; Singh, R; Al-Sultan, A; Wong, J; Menon, BK
Abstract : Background: Patients with acutely symptomatic carotid stenosis ("hot carotid") have high up-front risk of recurrent strokes. Uncertainties remain regarding optimal anti-thrombotic management, particularly while awaiting revascularization with endarterectomy or stenting (CEA/CAS). Methods: We administered a worldwide electronic survey through Neurology: Clinical Practice . Respondents chose their preferred antithrombotic regimen (1) in a general case of acutely symptomatic carotid stenosis, (2) if the patient was already on aspirin, or (3) had associated intraluminal thrombus(ILT). Responses among different groups were compared using multivariable logistic regression. Results: We received 668 responses from 71 countries. Most respondents favoured CEA(69.1%) over CAS, an aspirin-containing regimen(88.5%), and a clopidogrel-containing regimen(64.4%) if already on aspirin. Monotherapy was favoured by 54.4-70.6% across scenarios. The preferred dual therapy was low-dose aspirin(75-100mg) plus clopidogrel(22.2%), or high-dose aspirin(160-325mg) plus clopidogrel if already on aspirin(12.2%). Respondents favouring CAS more often chose ≥2 agents (adjusted odds-ratio[aOR] vs CEA: 2.00, 95%CI 1.36-2.95, p=0.001) or clopidogrel-containing regimens (aOR:1.77, 1.16-2.70, p=0.008). Respondents from Europe less commonly chose multiple agents (aOR vs United States/Canada: 0.57, 0.35–0.93, p=0.023) while those from Asia more often favored multi-agent regimens (aOR:1.95, 1.11–3.43, p=0.020). Conclusions: Our results highlight the heterogeneous anti-thrombotic management of hot carotids. Future trials should likely include high-dose aspirin monotherapy or low-dose aspirin/clopidogrel dual-therapy as a comparator arm to stimulate enrolment.